KEPATUHAN PAJAK DI SEKTOR UMKM BERDASARKAN UU NO 20 TAHUN 2008 TENTANG USAHA MIKRO, KECIL DAN MENENGAH - Gryani Elisabeth Purba; Santiana Siboro; Depi Yohana Manurung; Dewi Pika Lumban Batu; Arief Wahyudi (CV. ADIBA AISHA AMIRA, 2025)
Micro, small, and medium enterprises (MSMEs) have become a major part of the Indonesian economy. This business sector shows great potential to make a significant contribution. The annual increase in the number of MSMEs provides an opportunity for the government to focus its attention on this sector in order to increase tax revenue. The results of this study indicate that Tax Understanding, Tax Incentives, and Taxpayer Awareness have a significant positive influence on Tax Compliance for Micro, Small, and Medium Enterprises. Tax Understanding has a significant positive impact on tax compliance among Micro, Small, and Medium Enterprises. In addition, tax incentives and taxpayer awareness also have a significant positive influence on tax compliance for the micro, small, and medium enterprise sector. In mid-July 2013, the government issued a policy regulating special treatment regarding income tax for small, micro, and medium enterprises. This policy is known as Government Regulation No. 46 of 2013. This policy was designed to simplify tax obligations for taxpayers. Under this policy, taxpayers no longer need to calculate their profits, as the tax payable is directly calculated at 1% of total turnover. Small and medium enterprises play a significant role in Indonesia's economy; however, they still face several challenges in their development, such as market uncertainty, business sustainability, and unclear accounting systems. It is hoped that awareness, knowledge, and understanding of taxpayers regarding PP No. 46 of 2013 will improve their compliance in paying taxes, while penalties aim to encourage the public to comply and fulfil their tax obligations. Additionally, the quality of services provided by tax authorities also needs to be improved to encourage tax compliance. The purpose of this study is to determine the extent to which MSME actors are aware of, understand, and know about PP No. 46 of 2013, penalties, and service quality.